Excess perigestational folic acid exposure induces metabolic dysfunction in post-natal life - Keating, Elisa (2015)
The aim of this study was to understand whether high folic acid (HFA) exposure during the perigestational period induces metabolic dysfunction in the offspring, later in life. To do this, female Sprague-Dawley rats (G0) were administered a dose of folic acid (FA) recommended for pregnancy (control, C, 2 mg FA/kg of diet, n=5) or a high dose of FA (HFA, 40 mg FA/kg of diet, n=5). Supplementation began at mating and lasted throughout pregnancy and lactation. Body weight and food and fluid intake were monitored in G0 and their offspring (G1) till G1 were 13 months of age. Metabolic blood profiles were assessed in G1 at 3 and 13 months of age (3M and 13M respectively). Both G0 and G1 HFA females had increased body weight gain when compared with controls, particularly 22 (G0) and 10 (G1) weeks after FA supplementation had been stopped. G1 female offspring of HFA mothers had increased glycemia at 3M, and both female and male G1 offspring of HFA mothers had decreased glucose tolerance at 13M, when compared with matched controls. At 13M, G1 female offspring of HFA mothers had increased insulin and decreased adiponectin levels, and G1 male offspring of HFA mothers had increased levels of leptin, when compared with matched controls. In addition, feeding of fructose to adult offspring revealed that perigestational exposure to HFA renders female progeny more susceptible to developing metabolic unbalance upon such a challenge. The results of this work indicate that perigestational HFA exposure the affects long-term metabolic phenotype of the offspring, predisposing them to an insulin-resistant state.